The effect of low-dose spermidine supplementation on polyamine content and antioxidative defence mechanisms in honey bees - Spremo, Jelena; Vukašinović, Elvira; Kojić, Danijela; Kebert, Marko; Čelić, Tatjana; Đorđievski, Srđana; Purać, Jelena (Biologia Serbica, 2023)
The honey bee, a widespread pollinator, contributes to the conservation of biodiversity. In recent decades, a trend of declining colony numbers has emerged. The unsustainable exploitation of the environment may be the cause of this phenomenon. One protective strategy of organisms is to strengthen their antioxidative capacity. A class of positively charged molecules, polyamines, plays important roles in various cellular processes. They exert a regulatory effect on gene expression, have antioxidative properties, and promote longevity in model organisms. The three main representatives are putrescine, spermidine and spermine. The aim of this study was to determine whether supplementation of bees with low-dose spermidine leads to an increased level of the mentioned polyamines and whether this could strengthen the antioxidative defence system. Two experimental groups were established: C group (control), fed with a 50% (w/v) sucrose solution, and S0.01 group, whose diet was supplemented with 0.01 mM spermidine. The experiment lasted for 10 and 17 days. A significant increase in putrescine, spermidine and spermine content was noted in the supplemented group after 17 days, compared to its control. These results show a positive impact of spermidine supplementation on maintaining polyamine levels throughout aging. FRAP and MDA biochemical assays were used for the assessment of oxidative status. FRAP assay showed increased antioxidative capacity in the S0.01 group. These results are in accordance with the results obtained from the MDA assay, which showed a decreased level of lipid peroxidation in the supplemented group, in comparison to the control. The potential practical outcome of this study could be the use of spermidine in beekeeping practice to promote overall honey bee health.